Literature and medicine in the nineteenth-century periodical press : Blackwood's Edinburgh magazine, 1817-1858 - Coyer, Megan J. (Edinburgh critical studies in romanticism., 2017)
The first major study of the relationship between Scottish Romanticism and medical culture. In the early nineteenth century, Edinburgh was the leading centre of medical education and research in Britain. It also laid claim to a thriving periodical culture. Literature and Medicine in the Nineteenth-Century Periodical Press investigates how Romantic periodicals cultivated innovative literary forms, ideologies and discourses that reflected and shaped medical culture in the nineteenth century. It examines several medically-trained contributors to Blackwood's Edinburgh Magazine, the most influential literary periodical of the time, and draws upon extensive archival and bibliographical research to reclaim these previously neglected medico-literary figures. Situating their work in relation to developments in medical and periodical culture, Megan Coyer's book advances our understanding of how the nineteenth-century periodical press cross-fertilised medical and literary ideas.